Kebijakan Optimalisasi Pemungutan Pajak Daerah dalam Upaya Meningkatkan Pendapatan Asli Daerah Kota Bandung : Suatu Pendekatan Analytical Hierarchy Process - Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.08.TAHUN 2018, 2018)
The purpose of this study was to determine various factors in the ability of regional finances to increase own source revenue (PAD) sourced from local taxes and formulate various policy alternatives to increase own source revenue (PAD) sourced from local taxes in the City of Bandung. The research method used in this study is Analytical Hierarchy Process (AHP). Factors considered in determining regional financial capacity to improve regional finances, in particular the increase in local revenues derived from local taxes in the city of Bandung are: (1) increasing the flexibility of regional governments in planning development programs in the regions; (2) provision and improvement of the quality of public services to the community; (3) the role of tax which is classified as small in total regional revenues; (4) weak mechanisms and supervision and financial planning; (5) the lack of motivation and awareness of the public to pay local taxes; (6) administrative capacity of collection in areas that have not been effective. various alternative policies based on the order of priorities that might be implemented in an effort to improve regional finance, especially the increase in local revenue derived from local taxes in the city of bandung are: (1) increasing the efficiency of the administration of collection in the regions and reducing excessive collection costs; (2) expanding the base of local tax revenue and strengthening the collection process; (3) better implementation of supervision mechanisms and financial planning; (4) socialization and counseling to encourage public awareness in paying local taxes; (5) enlarge local taxing power.